O'Neil, Paul. Interview about his work as a CBC radio broadcaster, the school broadcasting program, and the history of radio in Newfoundland and Labrador. - Swain, Hector K. (1990)
Paul O'Neil talks about his career with the CBC in radio broadcasting, particularly the school broadcasting programs and their effect on the population of Newfoundland. O'Neil also discusses various other important radio programs at the time. 00:00 - Hector Swain introduces Paul O'Neil as having worked with CBC for many years; 01:35 - O'Neil talks about how he started his work with the CBC in 1953 working with school broadcasts; 05:58 - Setting up direct teaching broadcasts sending educational programs to communities; Teaching children who lived in lighthouses and other isolated areas without access to a school; Television education programs; Effect of the program on students and housewives; types of programs; 12:00 - Radios provided by the government; 13:50 - Talks about young teachers with a lack of education; 15:29 - What got him into radio communications; 17:30 - Travelling around the province talking to teachers and students about the program; 19:20 - O'Neil talks about the 4-H program; Religious broadcasting; 21:40 - The Gospel Singer with Max Young; Morning Devotions; The Religious Advisory Council; organizing a workshops for clergy who were broadcasting; Changes in religious broadcasting; 29:20 - The effect roads had on the need for religious broadcast programs; 31:00 - The Invitation to Worship program; 33:00 - The Lidstone Sister on VOCM; Harry Burton organ music on CBC; 33:35 - Gerald S. Doyle program; examples of announcements; Importance of that type of programs; Woodland Echoes; 37:20 - Talks about Christmas At program going to different communities; 40:00 - Talks about Shut-Ins with Bob Macleod; The Hospital Party for people in hospital and the sanitarium; 42:00 - Stamp Savings program to raise funds for war, and to teach children to save money; 42:50 - Talks about a Girl Guide program; 44:00 - Swain asks about Newfoundland radio resource material, books, articles; 47:20 - Talks about The Barrelman, the importance and quality of the program; 48:17 - Talk about the importance of the Uncle Mose ...